Economic Development for Empowering Local Communities - Prastiwi, Lustina Fajar; Priambodo, Magistyo Purboyo; Soseco, Thomas; Dwiputri, Inayati Nuraini; Sumarsono, Hadi; Qodri, Lutfi Asnan (KnE Social Sciences, 2024)
Srigonco Village is located in the southern region of Malang Regency. The village is directly adjacent to the south coast and the Southern Cross Route ( JLS), which can be a strategic location to drive the economic force toward raising tourism in Balekambang Beach. Using the Local Economic Development (LED) method, this research aims to map the potential of community-based villages in improving the economy. LED is an instrument for developing local resource-based economic activities for the welfare of the local communities. The result is From the four alternative scenarios, a scenario is estimated to be closest to predicting the situation in Srigonco Village, i.e., scenario IV. Unfortunately, this scenario drives the worst possible results compared to other scenarios. Some reasons for this selection are the minimal role of the government through Bumdes and the absence of MSMEs, which are supposed to use natural resource potential for their benefit. Keywords: Local Economic Development, villages, local communities